Separation of Manganese Metal Ions with Natural Zeolite Adsorbents and Activated Charcoal of Shall Water use Column Adsorption Method - Batrisya, Batrisya; Suyanta, Suyanta (Universitas Negeri Yogyakarta, 2020)
The purpose of this study is to determine the effectiveness of natural zeolite and activated charcoal to reduce levels of manganese in shall water, determine the effect of contact time with the effectiveness of separation of manganese metal in a shallow well water and know the condition before-after the adsorption process. Method that used was column adsorption with a flow system in which sample is applied to the filtration tube containing zeolite and active carbon. The tests carried out included testing of drinking water parameters namely pH and TDS, testing of manganese content in a shallow well water using Atomic Absorption Spectrophotometer (AAS). The results showed the effectiveness value of natural zeolite adsorbent and activated charcoal using an adsorption column to reduce manganese content in a shallow well water of 90.404%. The longer the use of natural zeolite and activated charcoal, the effectiveness of reducing the manganese content in a shallow well water tends to decrease. A shallow well water samples before the adsorption process have safe conditions for pH and TDS parameters, for manganese metal parameters are also still below the appropriate threshold (SNI) number 01-0220-1987 and RI Permenkes No.492 / MENKES / PER / IV / 2010, after the process of adsorption of f a shallow well water is safe for consumption.